A produção acadêmica sobre o componente curricular Filosofia no Ensino Médio (2004-2013) - Mineiro, Francisco Valmir Soares (2015)
This research, linked to the Graduate Program in Education: Curriculum of the Pontifical Catholic University of São Paulo - PUC/SP, of the research line Public Policy and Educational Reforms, has as main objective to draw an overview of the academic production on the Philosophy curricular component in High School, trying to identify what aspects, dimensions and characteristics can be distinguished from 2004 to 2013 production, in papers of scientific journals classified into A1, A2, B1 and B2 strata, and master's and doctoral theses. The specific objectives are: a) show aspects and peculiarities of academic production on Philosophy teaching at the secondary level of Basic Education in the 2004-2013 period; b) verify in what institutions and regions of Brazil the construction of knowledge on the subject has been more abundant; c) verify whether 2008 was a milestone in the increase of production on the subject; d) identify the commitment of the areas of Philosophy and Education with the production of knowledge on the Philosophy curricular component in High School. To achieve the proposed objectives, we used the methodological resource known as Knowledge of the State to identify the main themes that have marked the production of knowledge on the subject, as well as possible gaps and unexplored fields by the academic community on the Philosophy curricular component in High School. To address the numerous challenges presented at this stage of Basic Education, we counted on the contributions of Krawczyk (2009, 2011), Moehlecke (2012), Frigotto and Ciavatta (2003) and Carneiro (2012). Regarding the Philosophy curricular component, among others, we were guided by Severino (2009, 2010, 2011, 2012). To think about the attributions that emerge from the curriculum and its construction, we appealed to the reflections of Gimeno Sacristán (2000, 2002, 2013), Chizzotti and Ponce (2012), Moreira and Candau (2007). The study of the state of knowledge of academic production enabled to note the great contribution of the Education programs in the construction of knowledge about the Philosophy curricular component: 96% of production on the subject come from Graduate Programs in Education and 4% of the work from Philosophy Programs. We verified also that in the Southeast region a considerably larger number of academic works on the topic were produced, we highlight three centers: UNICAMP, PUC/SP and UNINOVE. After the enactment of the11,684/2008 Law, a broadening of the debate on Philosophy teaching in High School was set in the scientific community. The conquest for the legitimization of the curricular component; the consolidation of identity, as an autonomous curricular discipline, which only takes place in the action-reflection teaching practice, challenges to research on the presence of Philosophy in the Brazilian High School and how the academic community has positioned themselves about it. We advocate that the Philosophy curricular component develops its role and contributes to the formation of autonomous individuals